The Application of the Storytelling Method to Higher Order Thinking Skills (HOTS) of Indonesian Language Students in Grade V MI Ma’arif 01 Punggur Lampung Tengah - Azizah, Alvia Nurul; Muh Ngali Zainal Makmun; Lutfi Fadilah (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
Fifth-grade students of MI Ma'arif 01 Punggur in Central Lampung are the subjects of this research, which aims to examine how the storytelling approach can be used to enhance students' higher-order thinking skills (HOTS). This research was conducted using a two-cycle method known as Classroom Action Research (CAR). There are four phases in each cycle: preparation, implementation, evaluation, and reflection. Teachers and students were interviewed, and data were collected through assessments and observations. Menurut temuan penelitian, penggunaan storytelling di dalam kelas dapat membantu siswa lebih aktif terlibat dalam pembelajaran mereka sendiri, lebih memahami konsep-konsep kompleks, dan mengasah keterampilan analitis, kreatif, dan berpikir kritis mereka. Fifth-grade students at MI Ma'arif 01 Punggur improved their learning activities and outcomes when they used the storytelling approach, according to research findings. The learning activity in Cycle II increased by 54.55% from 55% in Cycle I to 85%. Further improvement is shown in the completeness of learning outcomes, which increased by 39.29% from 56% in Cycle I to 78% in Cycle II. Hasil penelitian menunjukkan bahwa penggunaan cerita untuk mengajar bahasa Indonesia dapat membuat siswa lebih terlibat dan meningkatkan pemahaman mereka. Hasil penilaian menunjukkan bahwa skor HOTS siswa meningkat di setiap siklus, yang menunjukkan perbaikan ini. Selain itu, pendekatan naratif juga mendorong lingkungan belajar yang menarik dan partisipatif. As a result, students in madrasah ibtidaiyah can benefit from storytelling, with students paying attention during the teaching and learning process, students' ability to analyze a story, students' ability to evaluate a story, and students' ability to retell a story as a PTK-based learning technique.